Extraction and characterization of nanocrystalline cellulose from oil palm empty fruit bunch and its potential as adsorbent for dye removal - Shanmugarajah, Bawaanii (2017)
Over the past few decades, enormous interest has been manifested in using biomass as a source of renewable energy and materials. Cellulose, in the form of Nanocrystalline Cellulose (NCC), gains prominence as a new nanostructured material. In this study, NCC was extracted from oil palm empty fruit bunch (EFB) via acid hydrolysis method. NCC was successfully extracted from EFB using 64 wt% sulfuric acid at 45°C for 45 min. The products obtained from each stage were characterized to confirm the removal of non-cellulosic components. In addition, Xray Diffraction (XRD) results disclosed that nanocrystals exhibited crystallinity index of 60%. On the other hand, Transmission Electron Microscope (TEM) showed NCC exhibited network like structure. It also showed that the native cellulose crystalline network region is approximately 20 nm diameter, while Dynamic Light Scattering (DLS) suggested NCC to have an average particle size of 291.4 nm. Following that, NCC was employed for Methylene Blue (MB) dye removal. Batch adsorption studies were carried out to analyze the effect of contact time, initial dye concentration, adsorbent dosage and agitation speed at a temperature of 30 ± 2°C. The obtained experimental data fitted well to Langmuir isotherm with monolayer adsorption capacity of 144.93 mg/g. Pseudo-second-order kinetic model provided a better correlation of the experimental data than others such as Lagergrens pseudofirst- order model. It was also found that intraparticle diffusion was not the only rate controlling step, instead, boundary layer diffusion was also contributing to the adsorption activity.